Kesehatan Terumbu Karang di Perairan Pulau Batanglampe Kabupaten Sinjai - Irfani Tahira; Andi Tenriawaruwaty A. R. Zulkifli; Ridha Alamsyah (Universitas Mataram, 2024)
Coral reefs are currently experiencing quite high pressure. Damage occurs everywhere causing ecological and economic functions to be disrupted. The impact of the damage will affect the level of health and threaten the sustainability of coral reef resources and their ecosystem. This research aims to determine the health level of coral reefs using indicators of live coral cover, algae cover, sand cover, mortality index and recovery potential. The method used is transect photos using CPCe (Coral Point Count with excel extension) software. The variables used in calculating the coral reef health index value use benthic component data. The health level of coral reefs is known by looking at live coral cover, algae cover, sand cover and the mortality index combined with the level of resilience. The results showed that the average live coral cover was 19.19% (poor). Average algae cover 29.60% (good), average sand cover 39.74% (good) and average mortality index 0.63% (high). The potential for restoration of the coral reef ecosystem on Batanglampe Island is included in the medium category. Community participation together with the Government is needed in maintaining and preserving the sustainability of the coral reef ecosystem in Sinjai Regency.